Impact of Entrepreneurial Motivation, Competence and Orientation on Business Performance: A Study on MSMEs in Kollam District of Kerala - Surendran, Remya; Alex, Sumi (International Journal of Psychosocial Rehabilitation, 2020)
This study addresses the relationship between entrepreneurial motivation, competence and orientation on organizational performance in the (Micro, Small & Medium Enterprises) MSMEs kollam district of Kerala. Entrepreneurial motivation, competence and orientation is an asset especially for those who are engaged in micro, small and medium enterprises and these factors becomes a crucial value to make a good business performance. This study further classified entrepreneurial motivation, competence and orientation into variables such as need for achievement, self-efficacy and external environment, technical competence, marketing competence, financial competence, risk taking, proactiveness, innovation that relates to organizational performance. The sample selected by utilizing purposive sampling technique and sample size is 200 owners of small and medium organizations in kollam district by using questionnaire. Both SPSS and MS Excel, correlation, multiple regression analysis were used for data analysis. The main findings of the study revealed that there was a positive relationship between entrepreneurial motivation, competence and orientation and organizational performance. The higher level of organization performance can be achieved through three factors such as entrepreneurial motivation, competence and orientation. All the managerial implications will help to managers of the small and medium scale organizations to making the decisions on behalf of achieving entrepreneurial goals and objectives. The study also suggested that incorporate other variables such as characteristics of the business environment, entrepreneurial behavior, market orientation, and other factors that affect business performance.